“Proyecto de factibilidad para la implementación de una empresa constructora de viviendas de bajo costo en la ciudad de Loja” - Cabrera González, César Alfonso (2024)
In response to the housing deficit in the region and the need for affordable solutions for low- and middle-income families, market, technical, administrative, economic, and financial studies were conducted. Each analysis was designed to evaluate the feasibility and sustainability of the project from multiple perspectives to ensure its success and contribute to the economic and social development of the city. The market study revealed a high unmet demand for low-cost housing. Among the 371 people surveyed, 56% expressed interest in acquiring affordable housing in the short term, with 60% considering prices under $50,000. The analysis showed that current housing supply is insufficient to meet this demand, as the local real estate market is geared toward higher-priced housing. These findings indicate a significant opportunity for a construction company offering affordable solutions aligned with the economic and social needs of low- and middle-income segments. The projected growth in unmet demand supports the relevance of this project as a viable and necessary alternative to address the housing deficit. The technical study assessed the installed capacity and infrastructure required for housing production. The installed capacity allows for an annual production of 36 housing units under extended work conditions, although the analysis considered only 33.33% of this capacity, based on an 8-hour workday. With efficient construction processes, the average time estimated for building each unit is 160 days, from planning to delivery. The study adopted the use of specific machinery and tools, such as concrete mixers and compactors, supplemented by a strategy of renting heavy equipment to reduce initial costs. The study concluded that the project is technically viable and that, by adjusting production capacity, it is possible to increase production to meet a larger share of projected demand. The administrative study defined a hierarchical organizational structure and a functions manual to ensure efficient project management. The organizational model consists of three levels: executive, advisory, and operational, with clearly assigned roles for each team member. This structure enables agile and coordinated decision-making, led by a General Manager and a Project Director. Additionally, the study analyzed the most suitable legal structure, recommending the Limited Liability Company (Cía. Ltda.), facilitating investor attraction and regulatory compliance. The company’s mission and values are centered on sustainability, 5 accessibility, and quality, which positions the organization as a committed actor in Loja’s urban development. This administrative approach supports not only operational efficiency but also the establishment of a strong, reliable corporate identity. The economic study detailed the initial investment, cost structure, and financial planning for project development. The total required investment amounts to $185,885.88, distributed among fixed assets, deferred assets, and working capital, which will need to be reinvested in 3- month cycles. The estimated annual production costs are $562,393.31, including land, construction materials, and labor. An analysis of asset depreciation and amortization was carried out to ensure long-term financial planning. Additionally, the unit construction cost was projected at $53,359.80 in the first year, adjusted to a sale price of $71,146.39, which includes a 25% profit margin. The study concluded that the cost structure is adequate and that project profitability can be optimized through efficient resource management and potential production capacity expansion. The financial analysis confirmed the project’s economic viability using indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), Benefit-Cost Ratio (B/C), and Payback Period (PRC). The calculated NPV of $180,293.29 and the IRR of 69.03% indicated profitability well above the 25% opportunity cost. The B/C ratio of 1.19 demonstrated that each dollar invested generates an additional return, confirming the project’s economic viability. The estimated PRC of 1 year and 7 months ensures a quick capital return, thereby reducing financial risk. Additionally, the sensitivity analysis showed that the project is resilient to fluctuations in production costs and income, reinforcing its adaptability to potential market changes.